2020
DOI: 10.3390/agronomy10040533
|View full text |Cite
|
Sign up to set email alerts
|

Response of Photosynthetic Performance to Drought Duration and Re-Watering in Maize

Abstract: The drought tolerance and capacity to recover after drought are important for plant growth and yield. In this study, two maize lines with different drought resistance were used to investigate the effects of different drought durations and subsequent re-watering on photosynthetic capacity, electron transfer and energy distribution, and antioxidative defense mechanisms of maize. Under short drought, maize plants decreased stomatal conductance and photosynthetic electron transport rate, and increased NPQ (Non-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 40 publications
(49 reference statements)
4
13
0
Order By: Relevance
“…This was reflected in the lower level of the PI ( total ) in this cultivar. The effects of drought stress observed in parameters PI ( total ) and RE 0 /ET 0 are in accordance with a previous report of Jia et al [44] in drought-stressed maize plants. (F v /F m ) known as maximum quantum yield of PS II represent the efficiency of PSII primary photochemistry.…”
Section: Discussionsupporting
confidence: 92%
“…This was reflected in the lower level of the PI ( total ) in this cultivar. The effects of drought stress observed in parameters PI ( total ) and RE 0 /ET 0 are in accordance with a previous report of Jia et al [44] in drought-stressed maize plants. (F v /F m ) known as maximum quantum yield of PS II represent the efficiency of PSII primary photochemistry.…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that prolonged drought damages the reaction centers photosystem I (PSI) and photosystem II (PSII). This is consistent with the findings of previous studies [ 57 ]. After well−watered conditions were met, the drought−tolerant cultivar LH 22 recovered more than the drought−sensitive cultivar ZM 366.…”
Section: Discussionsupporting
confidence: 94%
“…In general, PIabs and PItotal were lower at pod filling compared to flowering, suggesting that the photosynthesis responses of edamame during drought stress are growth stage-specific. Jia et al [ 38 ] also found that PSI and PSII activities declined with drought stress duration in maize. A decline in PIabs at pod filling suggests an inactivation of the PSII reaction centers (RCs) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A decline in PIabs at pod filling suggests an inactivation of the PSII reaction centers (RCs) [ 18 ]. Therefore, increased PIabs in AGS429 and UVE17 under drought stress shows that these cultivars may have maintained their PSII RCs and avoided photo-inhibition of both photosystems [ 38 ]. Although cultivars generally had higher PItotal under drought stress, AGS354 and UVE17 had a decrease in PItotal at flowering and pod filling, respectively.…”
Section: Discussionmentioning
confidence: 99%